Penerapan International Safety Management (ISM CODE) Pada PT AKR Sea Transport - Arrafi, Muhammad Alief; Syifa Fajar Maulani; Fikodias Gilang Prabowo; Lamanda Putri; Nurul Haqi Abdurroqib; Zharfany Putri Mila Julianto (Nama Jurnal Akmi, 2023)
The ISM Code or International Safety Management Code is an international regulation developed by the International Maritime Organization (IMO) to improve safety and reduce the risk of accidents on ships traveling around the world. This regulation regulates operational and administrative standards to prevent accidents at sea and protect the health and safety of crew, passengers, and the marine environment. The purpose of this study is to determine the application of the International Safety Management Code (ISM) on PT AKR's sea transportation. This research uses a qualitative descriptive method by conducting direct interviews with PT AKR Sea Transport personnel regarding the application of the ISM Code on the company's vessels. The results of the study indicate that PT AKR Sea Transport implements the ISM Code effectively and efficiently and has successfully met the requirements set out in the ISM Code. However, there are still some things that need to be addressed, especially related to the lack of awareness of company employees of the importance of implementing the ISM Code. This study concludes that the implementation of the ISM Code is important for the safety of PT AKR Sea Transport vessels and the welfare of employees and must be consistent and sustainable to maintain an optimal level of safety on company vessels